Atypical Pharyngeal Pouch Arising Bilaterally between the Hyoid Bone and Thyroid Cartilage - Lawrence J. Oh; Lyndon Chan; David Veivers (Case Reports in Otolaryngology)
Introduction. Pharyngoesophageal diverticuli are a common cause of dysphagia; they are associated with various morbidities and a decreased quality of life. There are several different types of the diverticuli, and they are divided based on the anatomical location of origin relative to the cricopharyngeal muscle; these include Zenker’s, Killian-Jamieson’s, and Laimer’s diverticula. The authors present a unique case of pharyngoesophageal diverticulum that has not been previously described. Case Presentation. A 65-year-old male presented with a 12-month history of dysphagia and odynophagia for solids. Barium swallow revealed bilateral moderately sized diverticuli that altered in size during the different phases of swallow. CT scan of the neck with oral contrast further identified the anatomy of the diverticuli, arising between the hyoid bone and thyroid cartilage. Discussion. An external transcervical approach was utilised to successfully repair the diverticuli. Subsequent cricopharyngeal spasm was treated with botulinum toxin, and the patient recovered with no ongoing symptoms. The barium swallow study is a commonly utilised initial investigation as it is easy to perform and safe and has good diagnostic value. Definitive management usually involves either endoscopic or open surgery. This case depicts a unique case of a pharyngeal diverticulum arising between the hyoid bone and thyroid cartilage.